Guar gum-modified magnetic palladium nanocatalyst: C–N coupling reaction and STAT3-Mediated breast cancer therapy - Junrui Luan; Xin Dong; Shuwen Zhou (Journal of Science: Advanced Materials and Devices)
The present study explains the unmoved synthesis of Pd nanoparticle-decorated guar gum utilized as Fe3O4 NPs (Fe3O4@guar gum/Pd NPs), the resultant catalytic and biological applications within the context of an eco-friendly procedure. FT-IR, FE-SEM, TEM, EDS, and so on are some of the methods applied to evaluate the constructional and physicochemical features of such an unequaled substance. After the characterization of the process, we successfully used the prepared Fe3O4@guar gum/Pd NPs in the N-arylation of indole across C(aryl)-N bond formation from the pertaining haloarens (I, Br, Cl) through Ullmann-type coupling reactions. In addition, the new accelerator bears the ability to be recuperated and recycled 7 times. The MTT test was then used to investigate the extent to which Fe3O4@guar gum/Pd NP-treated cells suppressed human breast cancer. Healthy (HUVEC) and breast cancer cells, specifically MCF-10, were used for the evaluation. The Fe3O4@guar gum/Pd NPs showed an IC50 value of 62 μg/mL against MCF-10, respectively. The presence of the material resulted in a 40–50% induction of cell apoptosis, along with down regulation of the anti-apoptotic marker. Finally, the Fe3O4@guar gum/Pd NPs showed suppressive properties on colony formation. According to our research, the Fe3O4@guar gum/Pd NPs can decrease STAT3 expression in the treated cells while increasing p53 levels. The effect of Fe3O4@guar gum/Pd NPs on human breast cancer cells demonstrates how important p53 and STAT3 are to the ensuing biological consequences. According to these findings, Fe3O4@guar gum/Pd NPs have a lot of promise as a therapy for human breast cancer cells.